DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS DI SMA N 11 KOTA JAMBI - Benar Sembiring, Diliza Afrila (Universitas Batanghari Jambi, 2017)
This research aimed to analyze (1) The influence of instructional communication to the economic learning result of students grade XI IPS MAN 11 in Jambi City, (2) The influence of learning motivation to the economic learning result of students grade XI IPS MAN 11 in Jambi City, and (3) The influence of instructional communication and learning motivation to the economic learning result of students grade XI IPS MAN 11 in Jambi City. There are 150 students as the population of this research. The proportional random sampling technique is used to choose the sample. There are 60 students grade XI IPS MAN 11 in Jambi City as the research sample. The data collected by distribution of questionnaire to the research respondent and documentation of learning result. The technique of data analysis is multiple regression with SPSS program Version 16. The research result shows that (1) Instructional communication a significant influence to the economic learning result of students grade XI IPS MAN 11 in Jambi City. It is shown by value of Sig. < 0,05, namely 0,000 < 0,05. As for the magnitude of the contribution variable instructional communication to the economic learning result of students grade XI IPS MAN 11 in Jambi City are 37,3%, (2) Learning motivation a significant influence to the economic learning result of students grade XI IPS MAN 11 in Jambi City. It is shown by value of Sig. < 0,05, namely 0,000 < 0,05. As for the magnitude of the contribution variable learning motivation to the economic learning result of students grade XI IPS MAN 11 in Jambi City are 38,8%, and (3) Instructional communication and learning motivation a significant influence to the economic learning result of students grade XI IPS MAN 11 in Jambi City. It is shown by value of Sig. < 0,05, namely 0,000 < 0,05. As for the magnitude of the contribution variable instructional communication and learning motivation to the economic learning result of students grade XI IPS MAN 11 in Jambi City are 43,9%. Keyword: Komunikasi Pembelajaran, Motivasi Belajar, Hasil Belajar